2006
DOI: 10.1073/pnas.0603728103
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression patterns define novel roles for E47 in cell cycle progression, cytokine-mediated signaling, and T lineage development

Abstract: In maturing T lineage cells, the helix-loop-helix protein E47 has been shown to enforce a critical proliferation and developmental checkpoint commonly referred to as ␤ selection. To examine how E47 regulates cellular expansion and developmental progression, we have used an E2A-deficient lymphoma cell line and DNA microarray analysis to identify immediate E47 target genes. Hierarchical cluster analysis of gene expression patterns revealed that E47 coordinately regulates the expression of genes involved in cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
134
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(140 citation statements)
references
References 45 publications
4
134
2
Order By: Relevance
“…For example, E47 degradation is regulated by Notch signaling and MAP kinase activity (King et al 2007). In lymphocytes, E2A proteins regulate proliferation and differentiation (Nutt and Kee 2007), and have been shown to regulate cell cycle factors, such as p57 and CDK6 (Rothschild et al 2006;Schwartz et al 2006). Two activation domains, AD1 and AD2, are located at the N-terminal half of the proteins and have both redundant and distinct functions.…”
Section: Discussionmentioning
confidence: 99%
“…For example, E47 degradation is regulated by Notch signaling and MAP kinase activity (King et al 2007). In lymphocytes, E2A proteins regulate proliferation and differentiation (Nutt and Kee 2007), and have been shown to regulate cell cycle factors, such as p57 and CDK6 (Rothschild et al 2006;Schwartz et al 2006). Two activation domains, AD1 and AD2, are located at the N-terminal half of the proteins and have both redundant and distinct functions.…”
Section: Discussionmentioning
confidence: 99%
“…[35][36][37] CDK6 is overexpressed in lymphoma, leukemia, glioma, glioblastoma, medulloblastoma, and cancers of squamous cells, salivary gland, bladder, pancreas and prostate. [38][39][40][41][42][43][44][45][46][47][48][49][50] In human prostate cancer cells, CDK6 has also been shown to bind androgen receptor and stimulate its activity in a kinase activity independent manner. 46 Blockage of CDK6 expression by microRNAs (miRNAs) has been shown to inhibit the proliferation of gliomas, medulloblastoma, prostate, bladder, gastric, hepatocellular, and lung cancer cells, indicating the significant role of CDK6 in the initiation and progression of these cancers.…”
Section: Introductionmentioning
confidence: 99%
“…MTG family members function in transcriptional repression, and therefore, these results imply that E-protein-mediated repression contributes to T-cell development. By comparing gene expression profiles from Mtg16 Ϫ/Ϫ LSK cells (M. Fischer et al, unpublished) to those of genes that were repressed by overexpression of E47 (21,42), we identified 19 genes that were repressed by E47 in hematopoietic progenitor cells but upregulated upon Mtg16 inactivation in LSK cells (see Table S1 in the supplemental material). In addition, we compared the changes in Mtg16 Ϫ/Ϫ gene expression profiles to those in genes regulated by overexpressed E47 in the context of Notch signaling from OP9-DL1 cells (see Table S2 in the supplemental material).…”
mentioning
confidence: 99%
“…The experiment was performed twice in triplicate. (C) Venn diagrams are shown that display the intersection between genes upregulated in Mtg16 Ϫ/Ϫ LSK cells relative to wild-type controls and genes upregulated by activated Notch signaling in OP9-DL1 coculture and E47 expression (left panel) (21) or E2A-deficient thymic lymphoma cells that were complemented by reexpressing E47 (right panel) (42 Tables S3 and S4 in the supplemental material). Of note, the expression of Mtg16, but not Mtg8 or Mtgr1, was activated by E47 (21), suggesting a possible regulatory loop between these proteins.…”
mentioning
confidence: 99%